SATURATED FATTY ACIDS IN ERYTHROCYTE MEMBRANES IN ADOLESCENTS WITH TYPE 1 DIABETES MELLITUS. (April 2021) - Marcon, Denise; Tagetti, Agela; Giontella, Alice; Monamì, Giada; Branz, Lorella; Bortolotti, Stefano; Piona, Claudia; Morandi, Anita; Trento, Laura; Minuz, Pietro; Maffeis, Claudio; Fava, Cristiano
Abstract : Objective: Type 1 diabetes mellitus (T1DM) is associated with early development of atherosclerosis. The aim of this study was to assess the association between saturated fatty acids (SFAs) contained in erythrocyte membranes and some indices of vascular damage in a sample of adolescents with T1DM. Design and method: Participants in regular follow-up at the Paediatric Diabetology Unit of Verona were sent for evaluation at the Vascular Laboratory of the General Medicine & Hypertension Unit Central blood pressure (BP), Pulse Wave Velocity (PWV) and Pulse Wave Analysis (PWA) were measured by the SphygmoCor Xcel, carotid Intima Media Thickness (cIMT) and carotid distensibility (DC) by ultrasound and elaborated with a dedicated hardware. Blood samples were evaluated for erythrocyte membrane SFA, expressed as a percentage of total Fatty Acids (FAs). Results: Hundred and forty-seven adolescents (78 males and 69 females, mean age 17, 25 ± 1, 93 years) were studied. Fifteen patients were classified as hypertensive (10, 2%) according to current European Guidelines. Thirteen patients had central systolic BP (cSBP) (8, 8%), 60 cIMT (40, 8%), 49 (33, 3%) DC and 1 PWV (0, 7%) above the 95th percentile for sex and age/height. We observed a correlation between total SFAs and cSB and z-cSBP (r = 0, 260 and 0, 269 respectively, p < 0, 05), not confirmed when each SFA was analysed separately. Furthermore, a positive correlation between total SFAs and either PWV or z-PWV was detectable (r = 0, 241 and 0, 251 respectively, p < 0, 05). The latter association remained significant even after adjustment for age, sex, Body Mass Index (BMI), duration of diabetes, HbA1c, total cholesterol, triglycerides-HDL ratio. Total SFAs were also associated with BMI (r = 0, 191, p < 0, 05). Conclusions: Erythrocyte membrane FAs are associated with vascular (cSBP and PWV) and anthropometric parameters in patients with T1DM. The amount of SFAs in membranes does not depend only on diet, as they are also neo-synthetized from glucidic precursors. Thus, it can be speculated that a bad glycemic control could translate into a higher substrate amount to produce the different SFAs. Further studies are needed to better understand the mechanisms and the regulations of these pathways